2015
DOI: 10.1309/ajcpe5nchwpsmr5d
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the 2013 ASCO/CAP HER2 Guideline Updates at an Academic Medical Center That Performs Primary HER2 FISH Testing

Abstract: Implementation of the 2013 ASCO/CAP HER2 guideline updates resulted in an increase in HER2 FISH equivocal results, which can be attributed to HER2 copy number, regardless of the HER2/CEP17 ratio. Reflex IHC for FISH equivocal cases is of limited utility; however, IHC does assign HER2 positivity or negativity in a small percentage of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 17 publications
6
35
0
2
Order By: Relevance
“…A recent study also showed that the percentage of Her-2 D-FISH equivocal cases was as high as 9.4% according to the ASCO/CAP 2013 guidelines [16], similar to our results. Several other studies also demonstarted a significant increase in the D-FISH equivocal cases after the ASCO/CAP 2013 guideline update [12,14,15,17,18]. In addition, our assay revealed the interpretation of D-FISH equivocal results with good reproducibility.…”
Section: Discussionsupporting
confidence: 63%
“…A recent study also showed that the percentage of Her-2 D-FISH equivocal cases was as high as 9.4% according to the ASCO/CAP 2013 guidelines [16], similar to our results. Several other studies also demonstarted a significant increase in the D-FISH equivocal cases after the ASCO/CAP 2013 guideline update [12,14,15,17,18]. In addition, our assay revealed the interpretation of D-FISH equivocal results with good reproducibility.…”
Section: Discussionsupporting
confidence: 63%
“…1,4 The number of such cases within a laboratory varies based on the patient population referred for ISH testing, but it seems to be approximately 5% of cases (range, 1% to 16%). 15,[19][20][21][32][33][34][35][36][37][38][39][40][41][42] The use of alternative probes to adjudicate these cases has also increased since 2013.…”
Section: Clinical Questionmentioning
confidence: 99%
“…In a laboratory using FISH for first-line testing, reflex HER2 IHC provided a clear positive or negative result in only 5 of 17 FISH-equivocal cases (29%). 17 In contrast, in a laboratory using first-line IHC, reflex FISH for 2þ IHC yielded a clear amplified or nonamplified result in 43 of 50 cases (86%). 18 It should be recognized that both IHC and FISH represent an attempt to convert a continuous biologic variable into a dichotomous category, an exercise that is clearly dependent on reproducible application of a validated cutoff.…”
Section: Test Methodologymentioning
confidence: 90%